Management of Female Infertility Through Mahakashaya (AYUSHDHARA, 2022)
In today’s world, infertility in women became a curse. The women who cannot conceive are the target of harassment, may be the hands of husband, in-laws or society in large. The problem of infertility is very common now a days and it has become essential need of the moment to find out solution which is, having less complication, efficient and affordable. Infertility is broadly described in ancient literature of our Ayurveda. In Charaka Samhita, fifty important Mahakashaya has been mentioned, Jeevaniya, Sandhaniya, Shukrajanan, Shukrashodhan and Prajasthapana, Mahakashaya are some of them, which drugs acts on different stages of infertility, and does Shodhan & Shaman of Doshas of reproductive system and of whole body, promotes strength and helps in conceiving. These drugs are of Rasayana in nature, which rejuvenates all body parts. The drugs of these Mahakashaya can be used either all together or individually or in permutation combination according to the patient’s condition. Female infertility arises due to disturbance in Ritu, Ambu, Beeja, and Kshetra. The main purpose of this paper is systematic study of these Mahakashaya on different stages of infertility especially on female and to examine the effect of drugs of Jeevaniya, Sandhaniya, Shukrajanan, Shukrashodhan and Prajasthapana Mahakashaya to collect the information on present studies on above mentioned factors.